An assessment of knowledge regarding hospital acquired infection prevention among health care workers in a government medical college, UP, India - Gupta, Rashmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: This study aimed to assess the status of knowledge and practice aspects regarding infection control and prevention among Health care workers in a tertiary health care facility of Uttar Pradesh. Methods: It was an observational cross section study conducted between April 2023 to June 2023 in a government medical college involving 179 health care workers. Data was collected on the basis of pre tested questionnaire through interview of health care workers. Questionnaire was divided into three-part, first part containing question related to demographic parameter of study participants and second and third part contained questions regarding knowledge and practice of standard infection control measures respectively. Results: Majority of participants were above 34 years (66.66%) female health worker (73.6%).72% participants were in the category of faculty member and nursing staff with average experience of more than 9 year. Study shows that100% of faculty members, resident doctors, and nursing staff were having the knowledge regarding steps of hand wash before surgical procedure and hand hygiene procedure before and after patient care. 100% of faculty members, resident doctors and nursing staff said that they perform all steps of hand wash before surgical procedure, perform hand hygiene before and after patient care. Conclusion: This study demonstrates a commendable level of adherence to infection control measures among healthcare workers. The high levels of compliance observed in our study may be attributed to institutional policies, ongoing training, or other factors unique to our setting.